Determinants of Performance in Smallholder Farmer Groups in Uganda - David Agole; Connie D. Baggett; John C. Ewing; Edgar P. Yoder; Margaret N Mangheni (Journal of International Agricultural and Extension Education, 2022)
The performance of farmer groups is critical for the success of the farmer-led Agricultural Extension approach currently used in Uganda. This study examines factors affecting performance of farmer groups accessing agricultural extension and advisory services from the National Agricultural Advisory Services in Eastern Uganda. The study collected data 200 members of 19 farmer groups in Eastern Uganda. Performance of farmer groups was the dependent variable, which was perceived to be influenced by individual members’ objectives, participation culture, power distance, structure of task, perceived equity, reward allocation and participation in group activities. Farmer group performance had a statistically significant positive relationship with power distance and perceived equity. Group participation culture and structure of tasks had a statistically negative relationship with group performance. Members tended to deflect group losses to factors beyond the seasonality of group activities, quality of farm inputs, and poor training delivered by advisory service providers. The advisory service providers and farmer group members need to use the political and social capital possessed by the local leadership, groups and community members for enhancing support and collective participation of the community in farmer groups. Since farmer groups are a sub-set of wider community, this empirical study brings into perspective the role of community culture in influencing performance of farmer groups in smallholder farming communities.
Keywords: Performance; participation culture; farmer groups; extension services; Uganda